Acute citrulline-malate supplementation and high-intensity cycling performance - Cunniffe, B.; Papageorgiou, M.; O'Brien, B.; Davies, N. A.; Grimble, G. K.; Cardinale, M. (The Journal of Strength and Conditioning Research, 2016)
Dietary L-citrulline-malate (CM) consumption has been suggested to improve skeletal muscle metabolism and contractile efficiency, which would be expected to predispose exercising individuals to greater fatigue resistance. The purpose of this study was to examine the effects of CM supplementation on acid-base balance and high-intensity exercise performance. In a double-blind, placebo-controlled, crossover study, 10 well-trained males consumed either 12 g of CM (in 400 ml) or lemon sugar-free cordial (placebo [PL]) 60 minutes before completion of 2 exercise trials. Each trial consisted of subjects performing 10 (×15 seconds) maximal cycle sprints (with 30-second rest intervals) followed by 5 minutes recovery before completing a cycle time-to-exhaustion test (TTE) at 100% of individual peak power (PP). Significant increases in plasma concentrations of citrulline (8.8-fold), ornithine (3.9-fold), and glutamine (1.3-fold) were observed 60 minutes after supplementation in the CM trial only (p = 0.05) and none of the subjects experienced gastrointestinal side-effects during testing. Significantly higher exercise heart rates were observed in CM condition (vs. PL) although no between trial differences in performance related variables (TTE: [120 ± 61 seconds CM vs. 113 ± 50 seconds PL]), PP or mean power, ([power fatigue index: 36 ± 16% CM vs. 28 ± 18% PL]), subjective rating of perceived exertion or measures of acid-base balance (pH, lactate, bicarbonate, base-excess) were observed (p > 0.05). This study demonstrated that acute supplementation of 12 g CM does not provide acute ergogenic benefits using the protocol implemented in this study in well-trained males.